(untitled) (Jurnal Online Pertanian Tropik, 2017)
Leaf scald (Xanthomonas albilineans) is an important pathogen of sugar cane in Indonesia and cause significant losses at several main sugarcane plantations. Some control measures, e.i. bactericides smeared Lysol 20% or alcohol 70% on cutting knife seedling for disinfectant, and hot water treatment at 50 minutes on 52,5áµ’C, have not given satisfactory results in managing this leaf scald in sugarcane on the field. Biological control with filtrate of endophytes bacterial were alternative to biocontrol agents Xanthomonas albilineans. The objectives of this research were to determine: influence of sterilization methods and endophytic bacterial filtrate dosages of sugarcane to control leaf scald (Xanthomonas albilineans). This research was conducted in Phytopathology Laboratory at the Faculty of Agriculture University of North Sumatra from April until December 2014. This research had done with Completely Randomized Design (CRD) with three-factor: 1. type of endophytic bacterial filtrates: filtrate of B2, B7 and B9 Sterilization methods of endophytic bacterial filtrate: control (no sterilization), Sterilization by autoclave and Sterilization by filter membrane, 3. Dosage of endophytic filtrate with four-level: 0,1%, 0,01%, 0,001% and 0,0001%. The result showed: 10 isolate endophytic bacteria had exploration were: B1, B2, B3, B4, B5, B6, B7, B8, B9, and B10. Three isolates had a clear zone on Petri dish â‰¥ 20 mm in vitro testing is B9, B7, and B2. The results showed that the membrane filter sterilization method was better when compared to autoclave sterilization, namely: the highest inhibitory zone diameter of endophytic bacteria in the treatment of B9 filtrate with a membrane filter sterilization method 0,1% at 3 days after inoculation that was equal to 23.00 mm.